Capturing the Understanding of Cultural Literacy in Prospective Elementary School Teacher Students: Bringing Culture into Education - Karimatus Saidah; Endang Sri Mujiwati; Rian Damariswara (Yayasan Keluarga Guru Mandiri, 2025)
Cultural literacy is a person's ability to understand, appreciate, and behave towards various cultures. Students must have cultural literacy skills to socialize, respect, and show tolerance towards different cultures in the institutional environment and the community. This study aims to reveal the understanding of the cultural literacy of PGSD students. The research method used is the mixed method with the explanatory sequential design. The study results showed that the cultural knowledge demonstrated by students was included in the good category, namely in language and arts literacy, multiculturalism, nationalism, and cultural inclusivity. They had the willingness to see and be involved in different cultures. However, the initiative and attitude towards different cultures were not seen in the results of this study. The conclusion of this study shows that students have a fairly good understanding of cultural literacy. This research contributes to how cultural literacy is implemented in lecture activities and how students understand cultural literacy, the importance of cultural literacy in higher education especially in elementary school teacher education to develop awareness of cultural differences to increase tolerance and the process of intercultural socialization.